The Effect of Health Education to The Active Presence of Mother to Take Their Toddlers to Posyandu - Maria Ulfa; Laily Prima Monica (STIKes Patria Husada Blitar, 2021)
The decrease of the active presence of toddlers at the posyandu has become a problem for health workers in monitoring the health and development of infants and toddlers in their working areas. This is due to several reasons, one of which is from the mothers who are lazy and do not know what is the benefits they will get when they are taken to the posyandu. The purpose of this study was to determine the effect of health education to the active presence of mothers to take their toddlers to posyandu. Methods: This study used a